2020
DOI: 10.3390/cancers12020467
|View full text |Cite
|
Sign up to set email alerts
|

Dual PI3K/mTOR Inhibitor NVP-BEZ235 Enhances Radiosensitivity of Head and Neck Squamous Cell Carcinoma (HNSCC) Cell Lines Due to Suppressed Double-Strand Break (DSB) Repair by Non-Homologous End Joining

Abstract: The PI3K/Akt/mTOR pathway is frequently altered in human papillomavirus (HPV)-positive and negative squamous cell carcinoma of the head and neck (HNSCC) and overstimulation is associated with poor prognosis. PI3K drives Akt activation and constitutive signaling acts pro-proliferative, supports cell survival, DNA repair, and contributes to radioresistance. Since the small molecule NVP-BEZ235 (BEZ235) is a potent dual inhibitor of this pathway, we were interested whether BEZ235 could be an efficient radiosensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
6
29
0
Order By: Relevance
“…Therefore, dual PI3K/AKT/mTOR inhibitors, such as BEZ235 and gdc-0980, are attracting increasing attention from researchers. BEZ235 is the first dual PI3K/mTOR inhibitor to enter clinical trials, the results of which show that the drug is well tolerated and has strong antitumour activity and is thus of substantial value for tumour treatment [81]. Studies on the PI3K/AKT signalling pathway as a targeted cancer therapy have been performed for more than a decade, and the Federal Drug Administration (FDA) has approved p110delta inhibitors for the treatment of certain types of lymphoma, providing hope for cancer treatment.…”
Section: Dual Pi3k/akt/mtor Inhibitorsmentioning
confidence: 99%
“…Therefore, dual PI3K/AKT/mTOR inhibitors, such as BEZ235 and gdc-0980, are attracting increasing attention from researchers. BEZ235 is the first dual PI3K/mTOR inhibitor to enter clinical trials, the results of which show that the drug is well tolerated and has strong antitumour activity and is thus of substantial value for tumour treatment [81]. Studies on the PI3K/AKT signalling pathway as a targeted cancer therapy have been performed for more than a decade, and the Federal Drug Administration (FDA) has approved p110delta inhibitors for the treatment of certain types of lymphoma, providing hope for cancer treatment.…”
Section: Dual Pi3k/akt/mtor Inhibitorsmentioning
confidence: 99%
“…Irradiation exposure can induce mitochondrial-dependent ROS generation [57]. ROS-modulated DNA damage repair [58][59][60][61], cell death regulation [62][63][64][65], tumor microenvironment [66,67], and CSC characteristics [67,68] greatly affect the radiotherapy efficiency. Among these biological factors, cell death and DNA damage are the most common aspects regulated by cellular redox status.…”
mentioning
confidence: 99%
“…Schötz et al observed radiosensitization in HNSCC cell lines, regardless of HPV-status. A DNA-repair defect was more apparent in the G1 than G2 phase and reporter gene assays pointed toward inhibition of non-homologous endjoining (NHEJ), but not homologous recombination (HR) ( 70 ). Chang et al also tested an alternative dual PI3K/mTOR inhibitor, PI-103, which caused radiosensitization comparable to dactolisib.…”
Section: Resultsmentioning
confidence: 99%